2011
DOI: 10.1007/s12010-011-9417-6
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary Studies for Cephamycin C Purification Technique

Abstract: A study was made for purification of cephamycin C from fermentation of Streptomyces clavuligerus. Initially, the culture broth was clarified by microfiltration and ultrafiltration, after which the resulting permeates were subjected to nonspecific adsorption and ion-exchange chromatography on resin columns. The antibiotic activity was measured by the biological method at each stage by assaying its activity against the Escherichia coli ESS, super sensitive to β-lactam antibiotic. The purification processes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A calibration curve was performed using ten cephalosporin C concentration values from 5 to 120 mg l -1 and 24 replicates for each concentration. Antibiotic analyses were also carried out via high-performance liquid chromatography as described in Baptista Neto et al [37]. Lysine and alpha-aminoadipic acid analyses were conducted by means of the post-column derivatization method with orthophtalaldehyde and quantified in a fluorescence detector [38].…”
Section: Methodsmentioning
confidence: 99%
“…A calibration curve was performed using ten cephalosporin C concentration values from 5 to 120 mg l -1 and 24 replicates for each concentration. Antibiotic analyses were also carried out via high-performance liquid chromatography as described in Baptista Neto et al [37]. Lysine and alpha-aminoadipic acid analyses were conducted by means of the post-column derivatization method with orthophtalaldehyde and quantified in a fluorescence detector [38].…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the purification of cephamycin C demonstrated the presence of other compound (or compounds), besides cephamycin C, in fermentation broth and that are detected by the bioassay method [13]. Rollins et al [16] reported the production of β-lactam compounds by the biosynthetic pathway of cephamycin C production in conditions of dissolved oxygen limitation.…”
Section: Resultsmentioning
confidence: 99%
“…Rollins et al [16] reported the production of β-lactam compounds by the biosynthetic pathway of cephamycin C production in conditions of dissolved oxygen limitation. Some of these compounds, like penicillin N, present antibacterial activity that may interfere in the determination of the cephamycin C concentration by biological methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain this antibiotic at an adequate purity level, the use of appropriate downstream techniques is essential to isolate it from the fermentation broth. Separation techniques based on adsorption and ion-exchange processes have been widely applied for the isolation and purification of products obtained during bioprocesses. These processes stand out from other separation techniques because they provide a high concentration factor, which satisfies the need for a high recovery of the product of interest . Moreover, they are nondenaturing, highly selective, and relatively inexpensive processes .…”
Section: Introductionmentioning
confidence: 99%